ANALISA PENERIMAAN DAN PENGELOLAAN DANA NASABAH PADA BANK JATENG CABANG KOORDINATOR MAGELANG - May Linda Nugraheni; Chaidir Iswanaji (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
ABSTRACT The purpose of this study was to determine the Acceptance and Management of Customer Funds at Bank Jateng, Magelang Coordinator Branch. This type of research is qualitative, because it puts more emphasis on the process that is taken from actual events, after which it concluded. The data in this research is the process of managing customer funds at Bank Jateng, Magelang Coordinator Branch. The data source of this research comes from an informant who was interviewed structurally. Based on the data analysis, it can be concluded that: (1) Receipt of customer funds at the Magelang Coordinator Branch Bank Jateng uses the accrual-based method. Funds received by the Magelang Coordinator Branch of the Central Java Bank can be in the form of demand deposits, savings deposits, and time deposits. These funds are collected from the community. (2) The management of customer funds at the Magelang Coordinating Bank Central Java shall use the cash-based method. Management of customer funds at Bank Jateng, the Coordinator of Magelang Branch in the form of loans, such as: Personal Loan (PLO), Small Business Credit (KUK), Multipurpose Credit, People's Business Credit (KUR), Kreditasalt Fur Wiederaufbau Credit (KFW), and additional business capital for family business activities. Keywords: qualitative; cash; personal loan; credibility alt fur wiederaufbau.